EXPERIMENTAL STUDY ON THE SEISMIC BEHAVIOR OF A SHEAR WALL WITH CONCRETE-FILLED STEEL TUBULAR FRAMES AND SLITS - Qing Han; Zeyu Gao; Yaohong Wang; Xin Wang; Zimo Bai (Civil Engineering Journal, 2018)
This paper proposes a new type of composite shear wall with concrete-filled steel tubular frames and artificial vertical slits. The seismic behaviour of this new shear wall is studied by using a cyclic loading test. The failure mode, load-carrying capacity, ductility, stiffness degradation, hysteresis behaviour and energy dissipating capacity shown in the course of the test are studied. And this paper proposes the calculation formula of normal section bearing capacity. The main research results are as follows. Firstly, the failure mode of this new shear wall is the flexural failure. Secondly, compared with the ordinary reinforced concrete shear wall with slits, the new shear walls with concrete-filled steel tubular frames and slits show a better performance in load-carrying capacity, ductility, stiffness degradation and energy dissipating capacity.